Analysis of Wave Tusing Patterns In Hadrah Art In Lubuk Dagang Village, Sambas District - Nurizki, Elvin; Olendo, Yudhistira Oscar; Silaban, Chiristianly Yery (Universitas Tanjungpura, 2024)
This study discussed the arts in Sambas, West Kalimantan, namely hadrah singing poetry praising the greatness of God and the 'Wave' drum pattern and techniques for playing the